Enhancement of photocurrent extraction and electron injection in dual-functional CH3NH3PbBr3 perovskite-based optoelectronic devices via interfacial engineering. (4th May 2018) - Tsai, Chia-Lung; Lu, Yi-Chen; Chang, Sheng Hsiung
Abstract: Photocurrent extraction and electron injection in CH3 NH3 PbBr3 (MAPbBr3 ) perovskite-based optoelectronic devices are both significantly increased by improving the contact at the PCBM/MAPbBr3 interface with an extended solvent annealing (ESA) process. Photoluminescence quenching and x-ray diffraction experiments show that the ESA not only improves the contact at the PCBM/MAPbBr3 interface but also increases the crystallinity of the MAPbBr3 thin films. The optimized dual-functional PCBM-MAPbBr3 heterojunction based optoelectronic device has a high power conversion efficiency of 4.08% and a bright visible luminescence of 1509 cd m −2 . In addition, the modulation speed of the MAPbBr3 based light-emitting diodes is larger than 14 MHz, which indicates that the defect density in the MAPbBr3 thin film can be effectively reduced by using the ESA process.